Territorial Cohesion Concept and Measuring: Territorial Impact Assessment of Regional Policies. The Case of the Campania Region - Filippo Bencardino; Angela Cresta; Ilaria Greco (Bollettino della Società Geografica Italiana)
The territorial cohesion is today the main European policy through which to reduce the economic-social, environmental and cultural imbalances between European regions, as well as a “tool” to measure, on the basis of geographic diversity, the level of cohesion achieved in terms of territorial impact assessment of the policies. The present paper, result of the second year of research of the PRIN 2015- Territorial Impact Assessment of the territorial cohesion of the Italian regions, aims to spread the results of the measure of territorial cohesion in the Campania Region in terms of Smart, Sustainable and Inclusive Growth (Europe 2020 Strategy), through the application of the innovative STeMA-TIA methodology to the regional system. The reading that the analysis returns, starting from the strategic objectives defined in the regional programming 2014-2020, shows a widespread weakness in the level of territorial cohesion reached (NUTS 2 and NUTS 3), but also suggests the most appropriate policy choices for the future, both in terms of strengthening the “virtuosity”, and in mitigating and recovering inefficiencies.